Pentingnya Pelayanan Informasi Berbasis Digital terhadap Pengguna Jasa Penerbangan di Bandar Udara Internasional Jenderal Ahmad Yani Semarang - Bunahri, Rifqi Raza; Bahtiar; Luwihono, Andung (Politeknik Penerbangan Jayapura, 2023)
This research aims to analyze the importance of digital-based information services for aviation service users at Jenderal Ahmad Yani International Airport in Semarang. The research method used is qualitative descriptive, collecting data through observations and interviews with passengers and airport staff. The results of the study indicate that passengers face difficulties in accessing information and there is a lack of personnel in the Customer Service department to serve passengers, thus requiring innovation in the form of a Virtual Customer Assistant (VICA) to facilitate passengers in obtaining desired information, as well as the addition of Customer Service personnel. Based on the findings of this research, it can be concluded that digital-based information services are crucial in enhancing the aviation service user experience at Jenderal Ahmad Yani International Airport in Semarang.